Patient-perceived Barriers to Rehabilitation at Physical Therapy Clinics: A Qualitative Insight (Asian Journal of Pharmaceutics (AJP), 2020)
Objective: This study was conducted to investigate patients perceived barriers to rehabilitation. Methods: Aqualitative study was designed using grounded theory and inductive approach that included a semi-structuredinterview checklist concerning patientsâ€™ perceived barriers to physical therapy service. The transcript wasanalyzed using ATLAS.ti software and a thematic analysis was conducted. Codes were generated and analyzed bysemantic linkages and network analysis. Results: A total of five themes were identified from qualitative analysis,namely, â€œtreatment results pain,â€ â€œout-of-pocket expenditure,â€ â€œlow perceived value for money,â€ â€œunavailabilityof caregiver,â€ and â€œunavailability of the therapist.â€ Conclusion: Apart from the barriers identified, a novel findingwas the perception of intergender treatment as a barrier by female patients. This phenomenon not only has socialimplications that may contribute adversely to clinical goals for that patient.